Protection or Restriction: An Analysis of the Blind Massage Policy for Employment Rights of Persons With Visual Impairments in China. (January 2022) - Li, Xue Hui; Xu, Su Qiong; Hu, Luan Jiao
Introduction: The United Nations Committee on the Rights of Persons with Disabilities identified the Chinese blind massage policy as "reserved employment" in its Concluding Observations in 2012. In response, this paper reviewed the policy on blind massage in China and discussed its effectiveness and social impact. Methods: Adopting a historical perspective, this paper describes the development stages of the blind massage policy in China. It reveals the social construction process of the blind massage policy. Government data were provided to help analyze the positive and negative effects of the policy according to the United Nations' Convention on the Rights of Persons with Disabilities. Results: The blind massage policy is a national strategy involving semi-reserved employment to improve the low employment rate of people with visual impairments in China. It promoted employment of people with visual impairments at the start, but, as the system of the blind massage gradually took shape, it restricted these individuals from choosing a career freely. The blind massage policy has resulted in deep-rooted social prejudices, and it demonstrates disability-based discrimination and charity-oriented practices. Discussion: The Chinese blind massage policy is discriminatory and does not reflect the modern concept of disability rights advocated in the United Nations' Convention on the Rights of Persons with Disabilities. Implications for Practitioners: The Chinese government needs to promote institutional reforms to provide better education and employment for people with visual impairments to change the limited content of vocational training and eliminate discriminatory policies.